Estudio jurídico y doctrinario del art. 45 de la ley orgánica de defensa del consumidor del Ecuador - Orbe Villalva, Jorge Washington (2014)
The consumer protection is one of the key issues of modern industrial society in which we live, called precisely as consumer society, a term that indicates the desire for goods and services that has engulfed the West after the deprivations Second World War. Consumers in this type of society, appear as the victims of a series of abuses, damages, against which the rules of common law are illusory protection. The right to compensation for damage. The consumer should receive advice and assistance in case of complaints suffered damages due to the purchase or use of defective goods or unsatisfactory services. You have the right also to just compensation for such damage through fast, efficient and inexpensive procedures. Thus it seeks to defend the rights of consumers, avoiding the violation of this guarantee by the people or suppliers. In view of the neglect of the competent authorities for attempting to disseminate information to citizens about their rights as consumers they have been run over by defects or faults that appear in the products, which by ignorance on the part of consumers about the products they buy to meet your needs , and you do not give them the satisfaction they expected result are violated their rights to this violation of the law, its enforcement should be very clear and non-compliance should be penalized and Repair and compensation for deficiencies, damage or poor quality of goods and services, and disruption of public services will be responsible , and this gives me a feasible to proceed to study the techniques and methodologies that I will use in research conducted problem as I have documents facilitate my research as the survey evidence, various citizens who have suffered this type of abuse.